2013
DOI: 10.4103/1658-354x.114072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea in surgical patients presenting to a tertiary care teaching hospital in India: A preliminary study

Abstract: Background:Obstructive sleep apnea (OSA) is often not diagnosed in patients presenting for surgical procedures thereby increasing the incidence of adverse perioperative course. Early diagnosis of this disease is important in modifying anesthetic management as well as utilizing specific means which may decrease the complications and improve the patient outcome.Methods:Patients greater than eighteen years of age, ASA I-III scheduled for elective surgical procedures under anesthesia were randomly selected. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The authors concluded that a high degree of suspicion and knowledge of association of OSA and medical diseases may help in detection of such cases and decrease the rate of perioperative complications thus improving patients' safety. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a high degree of suspicion and knowledge of association of OSA and medical diseases may help in detection of such cases and decrease the rate of perioperative complications thus improving patients' safety. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Given a prevalence of 2-9.4% of OSA in our population [2,19] , only 8/8,824 (0.09%) patients had diagnosed or treated OSA during the screening period in this cohort, suggesting gross underrecognition of OSA. While the actual [5,6,20,21] and points to the magnitude of this problem. Thus, the first recognition of OSA during preoperative evaluation is not an infrequent event.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that high-risk OSA (STOP-Bang ≥3) patients identified by the STOP-Bang questionnaire have higher BMI [18,23], higher ASA physical status [16,18,23], and increased comorbidities [16,18,23,37]. High-risk OSA (STOP-Bang ≥3) patients were older, had higher incidence of ischemic heart disease, heart failure, hypertension, dyslipidemia, arrhythmia, chronic obstructive pulmonary disease, hypothyroidism and diabetes mellitus [16,18,23,37].…”
Section: Stop-bang and Its Association With Medical Diseasesmentioning
confidence: 99%
“…High-risk OSA (STOP-Bang ≥3) patients were older, had higher incidence of ischemic heart disease, heart failure, hypertension, dyslipidemia, arrhythmia, chronic obstructive pulmonary disease, hypothyroidism and diabetes mellitus [16,18,23,37]. Screening with STOP-Bang and the knowledge of the association of OSA and comorbid diseases may decrease the rate of perioperative complications thus improving patients’ safety.…”
Section: Stop-bang and Its Association With Medical Diseasesmentioning
confidence: 99%